Dinâmica da paisagem na Microbacia do Riacho Cajazeiras no semiárido potiguar - Batista, José Pio Granjeiro (2012)
The semi-arid Northeast region are coming through changes since its formation causing changes in the landscape and increased degradation. The economic dynamics which was established at the Potiguar semiarid had for a long time settled in livestock, subsistence agriculture and cotton, however, these economies decline from the year 1970. Thus, the Potiguar spaces are undergoing by a process of space reordering marked by the growth of agricultural activities and the process of urbanization. In the Potiguar western region these changes weaken significantly transform the landscape. In these areas, the process of urbanization and agricultural activities have caused changes in the hinterland landscape changing the natural dynamics of the caatinga biome that has been subject to negative interference with the indiscriminate removal of vegetation. In this case, the specific study area of the watershed of Cajazeiras Creek located in the cities of Pau dos Ferros, Água Nova, Encanto and Rafael Fernandes, changes in the landscape has led to degradation and environmental fragility. From this perspective, the research objective is to assess the dynamics of the landscape of the watershed of Cajazeiras Creek, semiarid region of the state of Rio Grande do Norte, identifying the degrading factors, the most degraded areas and/or susceptible to degradation and environmental fragility. The research investigated the phenomena of light geosystems theory that emphasizes the integration of elements in shaping the landscape. During this reporting period, it was carried out exploratory and bibliographical research, and geoprocessing techniques to assess the social and environmental conditions of the researched area and its environmental fragility. To do so, first, it was made an multitemporal analisis on the basis of the years 1984, 1996 and 2009 demonstrating that the dynamics of use and land cover in the watershed of Cajazeiras Creek showed a significant change in the landscape, especially in the caatinga vegetation. This has been recovering in various areas of the watershed, especially in its upper course in the mountains of Bom Sera, in Encanto city. The analysis showed the need to develop policies and programs for the maintenance, restoration and preservation of the caatinga vegetation of the river network and of water bodies. In addition, it was identified the most degraded areas of the watershed, environmental fragility and potential emerging that take into account the landscape components such as climate, topography, geology, pedology, geomorphology and the use and occupation of the soil in an integrated manner. The results show that the landscape of the watershed has medium and high environmental fragility throughout its area, especially on the banks of the river network provided by the use and occupation of the soil in an inadequate way with the environmental conditions of the watershed